Batik motifs from 1957 until 2000 / Nur Nadia Mohd Salleh Anuar and Arbai'yah Abdul Aziz - Mohd Salleh Anuar, Nur Nadia; Abdul Aziz, Arbai'yah (2015)
This study will use the resources of the idea of looking back at the question and idea in their pattern motif in various ways and aspects, from 1957 until 2000 in Malaysia. This paper with great emphasis on the diversity of alternative resources. It will start with the past motifs design and later designs more directed to the designs in the form of more freely or abstract form. This option is based on the value of the line through drawing, color, appearance and shape that could be new knowledge for creating new motifs with certain design principles guided. The principles are explained while producing report on patterns and motifs in the presentation.